Characteristics of Ag-Doped ZnO Thin Films Prepared by Sputtering Method - Ngoc Anh, Tran Thi; Thi Ha, Tran; Viet Tuyen, Nguyen; Nguyen Hai, Pham (VNU Journal of Science: Mathematics - Physics, 2019)
This paper presents the preparation of Ag-doped ZnO bulk sample by solid state reaction and Ag-doped ZnO thin films by sputtering method. The effects of doping concentration (1, 2 and 4%) on the properties of the thin films were investigated. Various methods were utilized to investigate characteristics of the samples: X-ray diffraction, Raman scattering spectroscopy, photoluminescence, energy dispersive X-Ray spectroscopy, scanning electron microscopy, atomic force microscope, absorption spectroscopy and Hall measurement. The study results show that Ag diffused into ZnO crystal lattice after heat treatment at 1,200 o C. As-prepared thin film samples exhibited low resistivity in the order of 10 -3 Ω.cm. The film doped with 2% Ag shows the lowest resistivity of 1.8´10 -3 Ω.cm, which is potential for making transparent electrodes in optoelectronics.